THE POWERLESS ‘WITCHES’ OF JHARKHAND: QUESTIONING THE FAULTLINES IN LEGISLATIVE SAFEGUARDS (International Journal of Food and Nutritional Sciences, 2022)
The grave violation of human rights of women is of serious concern. Of the several human rights violations, the witch hunt violence against women ranges from less serious violence of stripping, parading naked, branding to more serious physical manifestations in the form of mob lynching, gang rape, cutting off body parts and even murder. In the absence of a Center specific law to punish witch-hunts, some states have enacted their own special anti-witch hunt laws, Jharkhand being the foremost among them. And where these laws are absent, the courts invoke other central criminal legislative provisions to tackle the violence committed in the garb of witch hunt because various facets of witch-hunt violence are not alien to other forms of legislature recognized violence. Despite these safeguards in place, age old practice of witch hunt violence against women continues to thrive in Jharkhand. The present research precisely analyses the contemporary situation to comprehend nihilities in legislative safeguards in protecting the powerless ‘witches’ of Jharkhand.